EKSPLORASI PERKEMBANGAN KEKUATAN OTOT LANSIA PASCA STROKE MELALUI TERAPI MENGGENGGAM BOLA KARET - Lucia Retnowati; Agus Setyo Utomo; Regina Rosca Putri Pertiwi (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Stroke is one of the leading causes of physical disability in the elderly, particularly related to muscle weakness and motor impairments. This study aims to explore the development of muscle strength in elderly post-stroke through grip ball therapy with a qualitative approach. The study involves two elderly post-stroke subjects selected using purposive sampling. Data were collected through in-depth interviews and observations, and analyzed using a thematic approach. The results show that grip ball therapy significantly improves muscle strength in the affected hand of both subjects. The first subject experienced an improvement in right-hand strength, enabling greater independence in daily activities. The second subject reported increased strength in the left hand, making it easier to perform daily tasks independently. Additionally, this therapy had a positive impact on the psychological condition of the subjects, such as feelings of satisfaction, confidence, and gratitude for the progress achieved. This study concludes that grip ball therapy is a simple, effective, and affordable rehabilitation alternative for elderly post-stroke individuals, particularly in areas with limited access to medical facilities. This therapy not only enhances muscle strength but also has a positive impact on the overall quality of life of the patients. Further research is recommended to explore the long-term benefits of this therapy and to integrate psychological aspects into stroke rehabilitation approaches